ٍSubject Review: Application and Usage of Pesticides in Palestine: Current and Future Outlook - Yacoub Batta (My University, 2003)
The present review paper was prepared due to the lack of reports or review articles which analyze and treat the problems resulting from the excessive use and application of pesticides in the Palestinian territories (P.T). It stated and discussed firstly the current status of pesticides application and usage in the P.T then, exposed at the problems created by the overuse of pesticides in these territories and then offered the proper solution of these problems at the present time and in perspective. Thus, it provided with a number of basic elements which may improve the present and future application and usage of pesticides in the P.T. It also urged to follow the necessary measures in order to solve the problems of pesticides overuse and hence to protect both local environment and national crop products from pesticide pollution. Moreover, certain examples were cited in this paper on fruitful regional cooperation between neighbouring countries as a solution of some cases of hard pest control on certain crops. Until present, such cases are treated only with excessive amounts of pesticides but, the proposed solution either reduces greatly the amount of applied pesticides for treating the pest or investigates non-pesticide control measure.